Loneliness, insomnia symptoms, social jetlag, and vitamin D deficiency in relation to mental health problems in Japanese female university students: a cross-sectional study - Nodoka Yamashita; Shioka Ishii; Yoriko Kotoku; Takuya Shuo; Hiromi Eto; Hideaki Kondo (Journal of Physiological Anthropology)
Abstract Background Vitamin D deficiency is highly prevalent among Japanese female university students. Vitamin D deficiency is associated with physical and mental health problems, including sleep disorders. This study aimed to clarify the relationship between vitamin D deficiency and sleep and mental health problems among Japanese female university students. Methods Participants were 224 female university students. Blood levels of 25-hydroxyvitamin D [25(OH)D] were measured using liquid chromatography-tandem mass spectrometry for vitamin D assessment. Mental health was assessed using the K6. Sleep–wake status as a factor related to mental health was assessed using the Athens Insomnia Scale (AIS) and Munich ChronoType Questionnaire. Loneliness was assessed using the Three-Item Loneliness Scale. Factors predicting mental health problems with a K6 score ≥ 5 were explored using the Mann–Whitney U test, Fisher’s exact probability test, and classification and regression tree (CART) analysis. Results The median (interquartile range) serum 25(OH)D concentration was 14.5 (11.8–18.3) ng/mL. Of the participants, 80.8% had vitamin D deficiency (25(OH)D < 20 ng/mL), and 26.3% had severe vitamin D deficiency (25(OH)D < 12 ng/mL). In total, 41.1% had mental health problems with a K6 score of ≥ 5. Although there was no significant association between vitamin D deficiency and sleep–wake problems, vitamin D deficiency was more prevalent among those with K6 scores ≥ 5 (P = 0.02). Compared to those with K6 < 5, those with K6 ≥ 5 had significantly higher Loneliness and AIS scores (P < 0.001), greater social jetlag (P = 0.03), shorter sleep duration on weekdays (P = 0.03), and lower serum 25(OH)D concentration (P = 0.02). In the CART analysis, the algorithm was set in the order of Loneliness score ≥ 6, AIS score ≥ 7, social jetlag ≥ 150 min, and serum 25(OH)D concentration < 14 ng/mL, and the target accuracy (95% confidence interval: CI) was 76.5 (70.3–81.9)%, and sensitivity and specificity (95% CI) were 62.2 (51.4–72.2)% and 86.3 (79.2–91.6)%, respectively. Conclusions Loneliness, insomnia symptoms, social jetlag, and vitamin D deficiency were associated with mental health problems among Japanese female university students.